Artist-led ensembles – an interview with Conor Mitchell, founder of The Belfast Ensemble - FitzGibbon, Ali (Irish Journal of Arts Management and Cultural Policy, 2021)
In the first Perspectives on Practice interview, Conor Mitchell speaks to Ali FitzGibbon about the establishment of artist-led The Belfast Ensemble and its civic and artistic purpose. The discussion explores the challenges and opportunities the Ensemble have encountered in their relationships with venues, festivals and audiences. The interview also considers how the Ensemble and Mitchell himself have negotiated their identity as ‘of Belfast’ and ‘of Northern Ireland’.